Axially loaded magnetic resonance image of the lumbar spine in asymptomatic individuals - Danielson, B; Willén, J (Spine (Philadelphia, Pa. 1976), 2001)
For this study, 43 asymptomatic individuals underwent magnetic resonance imaging of the lumbar spine in both supine psoas-relaxed position and supine axial compression in extension. The change in dural cross-sectional area between positions at each disc level was calculated. To evaluate the effect of axial loading on asymptomatic individuals, as compared with the effect on patients who have clinical signs of lumbar spinal canal stenosis, and to assess the effect that different magnitude and duration of the applied load have on the dural cross-sectional area. Degenerative changes in the spine are found in both symptomatic and asymptomatic individuals. A study of patients with suspected clinical lumbar spine encroachment examined in both psoas-relaxed position and axial compression in extension with computed tomographic myelography or magnetic resonance imaging of the lumbar spine is reported. A significant decrease in dural cross-sectional area was found, respectively, in 80% and 76% of the patients. The study subjects underwent magnetic resonance imaging examinations in both psoas-relaxed position and axial compression in extension. The examination of the subject under axial compression in extension was performed with the lumbar spine in a supine position using a compression device. Degenerative changes in and adjacent to the spinal canal were registered. The dural cross-sectional areas were determined for psoas-relaxed position and axial compression in extension, then compared. In seven reexamined individuals, the dural cross-sectional area was calculated after an axial load corresponding to 25% and 50% of their body weight and a loading time of 5 to 60 minutes. A significant decrease in dural cross-sectional area from psoas-relaxed position to axial compression in extension was found in 24 individuals (56%), most frequently at L4-L5, and increasingly with age. In four individuals (5 disc levels), a decrease in dural cross-sectional area to less than 100 mm2 from psoas-relaxed position to axial compression in extension was found. In seven reexamined individuals, a significant decrease in dural cross-sectional area was found: in five after 5 minutes load of 25% of their body weight, and in two with 50% of their body weight. Using magnetic resonance imaging, a significant decrease in dural cross-sectional area after axial loading was found less frequently in asymptomatic than in symptomatic subjects. The decrease was more frequent at L4-L5, and increasingly with age. The load should be 50% of the subject's body weight applied for at least 5 minutes.